2014
DOI: 10.1038/srep03912
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and massive gene expression shift marking adolescent transition in C. elegans

Abstract: Organismal development is the most dynamic period of the life cycle, yet we have only a rough understanding of the dynamics of gene expression during adolescent transition. Here we show that adolescence in Caenorhabditis elegans is characterized by a spectacular expression shift of conserved and highly polymorphic genes. Using a high resolution time series we found that in adolescent worms over 10,000 genes changed their expression. These genes were clustered according to their expression patterns. One cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 33 publications
(72 reference statements)
3
79
0
Order By: Relevance
“…To untangle the developmental effects from the effects of the bar-1 mutation, we used a time-series dataset23. We showed that bar-1(ga80) results in a slower development, as these worms take on average ~10% more time to develop than Bristol N2.…”
Section: Resultsmentioning
confidence: 99%
“…To untangle the developmental effects from the effects of the bar-1 mutation, we used a time-series dataset23. We showed that bar-1(ga80) results in a slower development, as these worms take on average ~10% more time to develop than Bristol N2.…”
Section: Resultsmentioning
confidence: 99%
“…The phenotype of N2 is distinct from wild strains in several ways, including aggregation behavior, maturation time, fecundity, body size, and many other traits [26, 27, 29, 3643]. The atmospheric oxygen concentration on agar plates is substantially higher than levels preferred by wild strains [4446], and laboratory oxygen concentration is a strong selective pressure on the organism.…”
Section: Selective Pressures: Nature Versus Laboratorymentioning
confidence: 99%
“…After cooling on ice for 1 min, the samples were pipetted into the cartridges, and the protocol as recommended by Promega was continued. After mRNA isolation, the "Two-color Microarray-based Gene Expression Analysis, Low Input Quick Amp Labeling" protocol, version 6.0, was followed, starting from step 5 (4,30,31).…”
Section: Methodsmentioning
confidence: 99%